Innate and adaptive type 2 immune cell responses in genetically controlled resistance to intestinal helminth infection. Issue 5 (4th February 2014) - Filbey, Kara J; Grainger, John R; Smith, Katherine A; Boon, Louis; van Rooijen, Nico; Harcus, Yvonne; Jenkins, Stephen; Hewitson, James P; Maizels, Rick M
Abstract : The nematode Heligmosomoides polygyrus is an excellent model for intestinal helminth parasitism. Infection in mice persists for varying lengths of time in different inbred strains, with CBA and C57BL/6 mice being fully susceptible, BALB/c partially so and SJL able to expel worms within 2–3 weeks of infection. We find that resistance correlates not only with the adaptive Th2 response, including IL‐10 but with activation of innate lymphoid cell and macrophage populations. In addition, the titer and specificity range of the serum antibody response is maximal in resistant mice. In susceptible strains, Th2 responses were found to be counterbalanced by IFN‐γ‐producing CD4 + and CD8 + cells, but these are not solely responsible for susceptibility as mice deficient in either CD8 + T cells or IFN‐γ remain unable to expel the parasites. Foxp3 + Treg numbers were comparable in all strains, but in the most resistant SJL strain, this population does not upregulate CD103 in infection, and in the lamina propria the frequency of Foxp3 + CD103 + T cells is significantly lower than in susceptible mice. The more resistant SJL and BALB/c mice develop macrophage‐rich IL‐4Rα‐dependent Type 2 granulomas around intestinal sites of larval invasion, and expression of alternative activation markers Arginase‐1, Ch3L3 (Ym1) and RELM‐α within the intestine and the peritoneal lavage was also strongly correlated with helminth elimination in these strains. Clodronate depletion of phagocytic cells compromises resistance of BALB/c mice and slows expulsion in the SJL strain. Thus, Type 2 immunity involves IL‐4Rα‐dependent innate cells including but not limited to a phagocyte population, the latter likely involving the action of specific antibodies.